PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. DYANDRA PROMOSINDO - Rafi Elmanda; Muhammad Reza Anwar Nurdin (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of work discipline and communication on employee performance PT. Dyandra Promosindo. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Dyandra Promosindo. The sampling technique of this study used simple random sampling. This study uses a sample size with the Slovin formula. Result work discipline and communication have positive and significant effect on the employees performance of PT. Dyandra Promosindo's, both partially and simultaneous.